Placenta Accreta in a Woman with Childhood Uterine Irradiation: A Case Report and Literature Review - Nanayo Sasagasako; Hirohiko Tani; Yoshitsugu Chigusa; Shingo Io; Haruta Mogami; Junzo Hamanishi; Akihito Horie; Eiji Kondoh; Yukiyasu Sato; Masaki Mandai (Hindawi Limited, 2019)
The pregnancies of childhood cancer survivors who have received uterine irradiation are associated with a high risk of several obstetrical complications, including placenta accreta. The present case was a 26-year-old pregnant woman with a history of myelodysplastic syndrome treated with umbilical cord blood transplantation following chemotherapy and total body irradiation at the age of 10. Despite every possible measure to prevent preterm labor, uterine contractions became uncontrollable and a female infant weighing 892 g was vaginally delivered at 27+4 weeks of gestation. Under the postpartum ultrasonographic diagnosis of placenta accreta, we selected to leave the placenta in situ. Although emergency bilateral uterine artery embolization was required, complete resorption of the residual placenta was accomplished on the 115th day postpartum. Our experience highlighted the following points. (1) The expectant management of placenta accreta arising in an irradiated uterus may not only fulfill fertility preservation, but may also reduce possible risks associated with cesarean hysterectomy. (2) Due to extreme thinning of and a poor blood supply to the myometrium, reaching an antepartum diagnosis of placenta accreta in an irradiated uterus is difficult. (3) The recurrence of placenta accreta in subsequent pregnancies needs to be considered after successful preservation of the uterus.